(untitled) (Світ фінансів, 2017)
Затонацька Т. Г. Проблеми бюджетного фінансування науки та освіти в Україні. Досліджено динаміку та стан бюджетного фінансування науки й освіти, обґрунтовано пропозиції щодо структури та обсягів цих видатків. Zanonas’ka T. The problems of budget financing of science and education of Ukraine. The article deals with dynamics and condition of budget financing of the science and education. The propositions of increasing of the effectives of such expanses are developed.